Towards Meaningful Physics Learning: Needs Analysis of an Inquiry-Based E-Module in Secondary Schools for Developing 21st-Century Students' Critical and Creative Thinking Skills - Fitri Sun Anjelika Sihombing; Yohandri (Jurnal Penelitian Pendidikan IPA, 2025)
Physics learning at the secondary school level is still largely dominated by theoretical approaches and lacks connection between physics concepts and real-life contexts. This condition hampers the development of students’ critical and creative thinking skills, which are essential competencies in the 21st century. Inquiry-Based Lesson is a student-centered approach that has proven effective in fostering these skills through scientific investigation processes. However, the use of digital learning materials based on Inquiry-Based Lesson, particularly in the form of physics e-modules tailored to the characteristics and needs of secondary school students is still very limited. This study aims to analyze the need for the development of Inquiry-Based Lessons physics e-modules from the perspectives of both students and teachers. The research adopts a qualitative descriptive approach, with data collected through questionnaires, interviews, and documentation studies in several secondary schools. The analysis results indicate that most teachers and students require digital learning materials that are interactive, contextual, and capable of systematically facilitating scientific inquiry activities. These findings provide a strong empirical foundation for the development of Inquiry-Based Lesson physics e-modules designed to enhance students’ critical and creative thinking skills and to promote more meaningful physics learning.